Growing Spatial Scales of Synchronous River Flooding in Europe - Wouter R. Berghuijs; Scott T. Allen; Shaun Harrigan; James W. Kirchner (Geophysical Research Letters)
Abstract River flooding is a common hazard, causing billions of dollars in annual losses. Flood impacts are shaped by the spatial scale over which different rivers flood simultaneously, but this dimension of flood risk remains largely unknown. Using annual flood data from several thousand European rivers, we demonstrate that the flood synchrony scale—the distance over which multiple rivers flood near synchronously—far exceeds the size of individual drainage basins and varies regionally by more than an order of magnitude. These data also show that flood synchrony scales have grown by about 50% over the period 1960–2010. Detrended flood synchrony values are serially correlated, implying that years with spatially extensive floods tend to follow one another. These findings reveal that flood risks are correlated well beyond the individual drainage basins for which flood hazards are typically assessed and managed.